Atividade Biológica de Extratos Orgânicos de Trichilia sp (Meliaceae) sobre Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) em Dieta Artificial - Matos, Andreia; Nebo, Liliane; Calegari, Elton Rodrigo; Batista-Pereira, Luciane; Vieira, Paulo; Fernandes, João; da Silva, Maria Fátima; Filho, Pedro Ferreira; Rodrigues, Ricardo Ribeiro (BioAssay, 2009)
The biological activity of organic extracts of leaves and twigs from three Trichilia species (Trichilia catigua A. Juss., Trichilia claussenii C. DC. and Trichilia elegans A. Juss.) was evaluated on Spodoptera frugiperda (J. E. Smith) development under laboratory conditions. Leaves and twigs of each plant species were dried and ground separately. Organic extracts were obtained with hexane, methanol and methanol/water at proportion of 1:1. The organic extracts (at 1000 mg kg-1) were incorporated into an artificial diet and offered to S. frugiperda during their larval period. The parameters evaluated were duration and mortality of larval and pupal periods and pupal weight. The hexane and methanol extracts of leaves and the hexane extract of twigs of T. claussenii caused the highest larval mortality (above 60%). The extracts of T. elegans, T. claussenii and T. catigua retarded the larval development in 2.0; 1.3 and 3.2 days, respectively. All extracts did not affect the pupal period. Except for the hexane extract of T. claussenii, all extracts caused significant reduction in the pupal weight in comparison to the control. Among the three species of Trichilia tested, the hexane and methanol extracts of leaves and hexane extract of twigs of T. claussenii are the most promising for controlling S. frugiperda.